Analytical Modelling of Textile Parameters and Draping Behaviour of 2D Biaxial Braided Sleevings. Issue 5 (June 2017) - Schillfahrt, Christian; Schledjewski, Ralf
Biaxial braided sleevings are commonly used for producing hollow complex-shaped composite parts through bladder inflation moulding. To enable feasibility analyses, part design and the prediction of mechanical properties of the resulting fibre-reinforced component, various geometrical and weight-related parameters of the braided fabric in its draped state must be known, such as fibre orientation, fibre volume fraction and areal weight. In the present work, a comprehensive analytical model describing fabric formation, preform architecture and weight as well as the change of relevant textile parameters of a biaxial braided sleeving during draping is established. The principal modelling approach is based on sporadic investigations found in literature and was substantially expanded to compile an extensive collection of relationships for the utilisation in a sleeving-on preforming process. Furthermore, a critical overview about the state of the art in the area of geometrical modelling of tubular 2D braided structures and a comparison of the identified procedures in regard to the desired application is given.